PENGOLAHAN SAMPAH ORGANIK MENGGUNAKAN MAGGOT BSF (Black Soldier Fly) DI BANK SAMPAH SULTAN TANJUNG LINGKUNGAN KARANG SUKUN, KELURAHAN TANJUNG, KECAMATAN LABUAN HAJI, LOMBOK TIMUR - Bayu, Giri; Islam, Lalu Azan; Fauzi, M. Taufik; M.Ardinata; Nabila; Zain, Ihsani Nurmayanti; Hidayat, Syarif; Hanifatunnida, Ria Safna; Rohaniah; Sajidah, Hanna Risma; Ijtihad, Manarul (Universitas Mataram, 2024)
Organic waste is still a problem in Indonesia due to the increasing population and the problem of waste processing is still not resolved. Waste processing requires proper handling to decompose waste generation, especially organic waste. The aim of this activity is to describe the use of Black Soldier Fly (BSF) in processing organic waste. The method of this activity is a demonstration plot technique which can be used as a place of learning for the community to improve their knowledge and skills. The result of this activity is that it can reduce organic waste originating from markets, households and restaurants, thereby reducing the amount of organic waste produced. In conclusion, the use of maggots in processing organic waste can reduce organic waste disposed of at TPS.